EP 64. Altered default mode: resting-state functional connectivity changes in response to social stress. Issue 9 (September 2016) - Clemens, B.; Wagels, L.; Bauchmüller, M.; Bergs, R.; Schneider, F.; Habel, U.; Kohn, N.
Abstract : Up to now it remains unclear how stress in a social context affects the resting human brain, as assessed by functional magnetic resonance imaging (fMRI). Here, we compared for the first time resting-state functional connectivity in a large sample of healthy volunteers before and after the cyberball task. Of primary interest were the salience resting-state network (RSN), the executive control RSN and the default mode network (DMN), because these networks have been proposed to show a marked stress response. The DMN exhibited increased resting-state functional connectivity with several regions following the cyberball task. These regions included the key nodes of the salience RSN, the dorsal anterior cingulate cortex (dACC) and the anterior insula, as well as sensorimotor regions and higher-order visual areas. We conclude that the increased connectivity of the DMN with key nodes of the salience RSN and regions responsible for preparatory motor activity and visual motion processing indicates an adaptation of the default mode of brain function, which is shifted towards a more vigilant and attentive mode. This adaptation, or network re-set, symbolizes the brains response to the social stress, enabling participants to better reorient attention, detect salient external stimuli, and deal with the emotional and affective consequences of social stress. In line with previous studies, we provide first experimental evidence for the modulatory influence of social stress on the stability of RSN. If further substantiated, this finding may also have implications for psychopathological alterations of the stress response in a social context as in many psychiatric disorders. Therefore, future studies should investigate whether comparable findings might be obtained in clinical populations, and how stress-induced changes in resting-state functional connectivity relate to symptom severity and individual differences in resilience and stress-coping strategies.